Smart Alignment of Wireless Charger System of Electric Vehicle Using Image Processing - M.Nagarajan, S.Divyapriya (International Journal of Advanced Science and Technology, 2020)
Electrical vehicle charging is done by either wired or wireless chargers. In wired type of charging there is a metal contact between the electric vehicle supply equipment and the charging inlet of the vehicle. In wireless type of charging electric vehicles there is no physical contact between the charging inlet of vehicle and the supply equipment. Since there is no physical contact between the electric vehicle and the charging equipment attainment of lossless energy sharing is a challenge. There occurs an energy loss while charging, when the electric vehicle is not parked in correct alignment with the charging equipment. This project deals with automatic alignment of the wireless charger equipments through image processing technique.The wireless charging of electric vehicle is based on near-field wireless power transfer technology. The near-field wireless power transfer systems are of two types: Inductive charging and Capacitive charging. In inductive charging magnetic field coupling is produced between the conducting coils whereas in capacitive charging electric field coupling is used to transfer energy between the conducting plates. In both cases attainment of maximum and efficient energy transfer is a challenge due to coupler’s relative position changes. Thus the vehicle has to be in proximity to the charging plates or coils.In this project a hydraulic slide is employed with the charging equipment. Through digital image processing technique the proximity is calculated and the digital output is fed to the hydraulic slider. Based on the output the sliderinterfaced with the charging equipments gets aligned. The overall process is controlled by a microcontroller unit and thus energy loss due to improper alignment is neglected.